2020
DOI: 10.3892/ol.2020.12223
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑454‑3p inhibits cell proliferation and invasion in esophageal cancer by targeting insulin‑like growth factor 2 mRNA‑binding protein 1

Abstract: Esophageal cancer (ESCA) is the eighth most common cause of cancer-associated mortality in humans. An increasing number of studies have demonstrated that microRNAs (miRs) serve important roles in mediating tumor initiation and progression. miR-454-3p has been found to be involved in the development of various human malignancies; however, little is known about the role of miR-454-3p in esophageal cancer. In the present study, the protein and gene expression levels of miR-454-3p in ESCA tissues and cells were do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 35 publications
(39 reference statements)
0
18
0
Order By: Relevance
“…In addition, low miR-454-3p expression in bladder cancer tissues, predicted poor prognosis of bladder cancer patients ( 14 ). Moreover, miR-454-3p functioned as a tumor inhibitor of esophageal cancer by inhibiting the ERK/AKT signaling pathways ( 35 ). With regard to NSCLC, the expression of miR-454-3p was downregulated in NSCLC tissues and cell lines ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, low miR-454-3p expression in bladder cancer tissues, predicted poor prognosis of bladder cancer patients ( 14 ). Moreover, miR-454-3p functioned as a tumor inhibitor of esophageal cancer by inhibiting the ERK/AKT signaling pathways ( 35 ). With regard to NSCLC, the expression of miR-454-3p was downregulated in NSCLC tissues and cell lines ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although many of the cancer-related mRNA targets of IGF2BP1 were found to promote cell proliferation, migration and invasion [32,33,44], several were shown to take part in indirect suppression of tumor growth and metastasis [45,46]. We found that IGF2BP1 is required for gemcitabine resistance, and that RRP9 interacts with IGF2BP1, leading to reduced apoptosis and increased growth in PC cells.…”
Section: Discussionmentioning
confidence: 86%
“…In contrast, inhibition of miR-454-3p up-regulated PTEN expression, but attenuated the phosphorylation of AKT and mTOR, resulting in resensitization to oxaliplatin. Notably, previous studies reported that miR-454-3p inhibited AKT signaling pathway by targeting insulinlike growth factor 2 mRNA-binding protein 1 (IGF2BP1) in esophageal cancer (ESCA) ( 35 ) and targeting c-met in nasopharyngeal carcinoma ( 36 ), resulting in the suppression of cell growth and enhancement of cisplatin sensitivity. These inconsistent results may indicate that the role of miR-454-3p in modulating tumor progression and chemotherapeutic sensitivity was dependent on the types of human malignancies.…”
Section: Discussionmentioning
confidence: 99%